"I Try to Keep That Sugar Down." Experiences of Homebound Older Adults With Type 2 Diabetes: Barriers to Self-Management. Issue 1 (2nd January 2020) - Bustillos, Brenda Diane; Sharkey, Joseph Richard
Abstract: Objectives: To study the experiences and challenges of type 2 diabetes (T2D) self-management among homebound older adults who regularly receive home-delivered meals and services. Methods: Participants ( n  = 31) were recruited by telephone screening and were selected by purposive sampling. Semi-structured interviews were subsequently conducted within participants' homes. The interpretive methodology utilized in this study was developed to systematically assess T2D self-management. Results: Thematic analysis shows that participants felt mostly responsible for their health status, but attributed any noncompliance to lack of social and economic assistance. Most of the seniors in this study felt competent, but often did not have the opportunity to engage in protective measures due to a number of economic, physical, and social barriers. Conclusions: These results contribute to a better understanding of how to approach, support, and motivate homebound older adults with T2D while addressing challenges. Findings offer insight into the development of diabetes self-management education (DSME) and interventions for this population.